Development of a mathematics instructional media by utilizing geogebra to enhance junior high school students’ Higher order thinking skills - Ma’rufi Ma’rufi; Muhammad Ilyas; Shandy Agung; Ikram Lihu (Universitas Negeri Makassar, 2020)
This study aimed to develop an interactive visual media called Geoactive (Geogebra interactive) by employing Geogebra to improve students higher order thinking skill (hots) in the learning of solid geometry. The media was developed by using the model of 4D from Thiagarajan, which consists of define, design, develop, & disseminate. The product testing was conducted in SMPN 2 BUA, and two validators validated the product. Results show that: (1) the Geoactive developed was declared valid with the average assessment score of 4.45 which was in the category of very good; (2) the interactive media developed was declared practical with its indicator of the average of learning implementation being 78.67% which was in the category of good and the score of students’ response was 2.89 which was categorized as good; (3) the Geoactive developed was effective with the completeness indicator of conceptual understanding and problem solving was 77,14% and 71,43%, respectively. Both of the two scores were categorized as high